ENGINEERING STUDENTS PERSON-ENVIRONMENT FIT: A COMPARISON STUDY OF TWO PUBLIC HIGHER LEARNING INSTITUTION IN MALAYSIA - Ahmad Rozelan, Yunus; Amir, Aris (2012)
This study was conducted to determine the congruency between the type of student personality and the type of environment area of specialization based on Holland’s Individual-Environmental Congruence Theory among engineering students of two universities in Malaysia. The subjects of this study were 276 students who were selected using the purposive random sampling of engineering program students who enroll into business or entrepreneurship as their elective course. The instrument used in this study was the Holland’s Self-Directed Search (SDS). The finding of this study showed that there was no significant congruence between the type of student personality and their area of specialization. The finding of this study also showed that there was a significant difference in personality between male and female student of engineering program in one of the university, but there was no significant difference in personality between male and female student of engineering program in the other university. Generally the finding of the study showed that the engineering students had chosen the area of specialization that is not congruent to their personality. In view of the findings, several implications and recommendation were put forward.